Increased Brain Iron Detection by Voxel-Based Quantitative Susceptibility Mapping in Type 2 Diabetes Mellitus Patients With an Executive Function Decline - Li, Jing; Zhang, Qihao; Zhang, Nan; Guo, Lingfei (Frontiers in Neuroscience, 2021)
Purpose Brain iron accumulation has been suggested as a pathomechanism in patients with type 2 diabetes mellitus (T2DM) with cognitive impairment. This research aims to examine the total-brain pattern of iron accumulation in relation to executive function decline in patients with T2DM by voxel-based quantitative susceptibility mapping (QSM) analysis. Methods Thirty-two patients with T2DM and 34 age- and sex-matched healthy controls (HCs) were enrolled in this study. All participants underwent brain magnetic resonance examinations and 48 individuals underwent cognitive function assessments. Imaging data were collected with three-dimensional fast low-angle shot sequences to achieve magnitude as well as phase images. Using voxel-based QSM analysis, we compared the voxel-wise susceptibility values of the whole brain among groups and explored whether the mean susceptibility values of detected regions had correlations with cognitive data. Results Among the 66 participants, cognitive function was estimated in twenty-three patients with T2DM (11 males, 12 females; average age, 64.65±8.44 years) and 25 HCs (13 males, 12 females; average age, 61.20±7.62 years). T2DM patients exhibited significantly (t=4.288, P<0.001)] lower Montreal Cognitive Assessment (MoCA) scores [T2DM, 27 (27, 28); HCs, 29 (28, 29); normal standard ≥26)] and higher Trail-making Test (TMT)-A/TMT-B scores [71 (51, 100)/185 (149, 260)] than HCs [53 (36.5, 63.5)/150 (103, 172.5)] (Z=2.612, P=0.009; Z=2.797, P=0.005). Subjects with T2DM showed significantly higher susceptibility values than HCs in the caudate/putamen/pallidum, frontal inferior triangular gyrus, and precentral gyrus on the right hemisphere and in the caudate/thalamus on the left hemisphere. In contrast (HC > T2DM), no region showed a significant difference in susceptibility values between the groups. After multiple comparison correction, the right frontal inferior triangular gyrus/middle frontal gyrus/inferior frontal gyrus showed a significant relationship with TMT-A (R2=0.35, P=0.024).The right frontal inferior triangular gyrus/inferior frontal gyrus and right putamen/pallidum showed a significant relationship with TMT-B (R2=0.32, P=0.014; R2=0.33, P=0.008). Conclusion Patients with T2DM presented declined cognitive assessments and elevated iron deposition in the thalamus, striatum and frontal lobe, suggesting that executive function decline in T2DM might be associated with the cerebral iron burden.